Transformation Of Islamic Education In The 19th Century: The Struggle Between Tradition And Modernity - Kelana, Hendri; Alfauzan Amin; Saepudin (El-Ghiroh : Jurnal Studi Keislaman, 2026)
The transformation of Islamic education from the nineteenth to the early twentieth century marked a crucial phase in the intellectual and institutional development of the Muslim world. This period was characterized by a dialectical encounter between the preservation of classical Islamic traditions and the growing demand for educational modernization in response to colonial expansion, scientific progress, and global intellectual reform movements. This study aims to analyze the dynamics of Islamic educational transformation through the interaction between traditional values and modern educational ideas in both the broader Muslim world and Indonesia. This research employs a qualitative historical approach based on library research, utilizing primary and secondary scholarly sources relevant to the period under study. The findings reveal that Islamic educational reform was significantly influenced by major reformist figures such as Jamal al-Din al-Afghani, Muhammad Abduh, and Muhammad Rashid Rida, whose ideas later shaped the development of Islamic educational institutions in Indonesia, including pesantren and madrasah systems. The study contributes to the discourse on Islamic studies by demonstrating that the transformation of Islamic education was not merely a process of Westernization, but rather a negotiated synthesis between tradition and modernity that continues to influence contemporary Islamic education.